Study skills toolkit for students with dyslexia - Gribben, Monica (Los Angeles : SAGE, 2012)
This title provides ideas and advice to help dyslexic students with their studies. Packed with helpful advice, hints, checklists and templates, this book will help you improve your study skills throughout your time at university.
1. Stepping out into university with dyslexia -- 2. Procrastination -- 3. Note-taking -- 4. Understanding your assignment -- 5. Gathering information -- 6. Thinking critically -- 7. Writing your assignment -- 8. Writing your dissertation -- 9. Referencing -- 10. Exams -- 11. Oral presentations -- 12. Making the most of your feedback.
Includes bibliographical references (page 189) and index.
Keywords: Dyslexics -- Education (Higher); Reading disability; College students with disabilities; Learning disabled -- Education (Higher); Dyslexia; Study skills; College students with disabilities; Dyslexia; Dyslexics -- Education (Higher); Learning disabled -- Education (Higher); Reading disability; Study skills